KEDISIPLINAN DAN ETOS KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA SERTA DAMPAKNYA PADA GOOD GOVERNANCE - Zuraidah Zuraidah; Sri Anugrah Natalina (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2020)
The Regional Government has an obligation to report the results achieved in carrying out activities in a systematic and structured manner during a reporting period. The State Civil Apparatus in the Regional Government of Kediri Regency based on the above calculation results, it can be seen that the value of the direct influence X1 on Z is 0.417 and the value of the non-influence is 0.147 which means that the value of the direct influence is greater than the indirect effect. So it can be concluded that directly X1 against Z has a significant effect. The value of X2 on Z direct effect is 0.291 and the value of the indirect effect is 0.150, which means the value of direct influence is greater than the indirect effect. So it can be concluded that directly X2 on Z has a significant effect. The Kediri district government showed that the good governor was good enough. Public accountability does not show any problems in the performance of the institution / government which are publicly revealed, in its transparency it illustrates the existence of a decentralized pattern in the implementation of work programs in each SKPD so that accountability among SKPDs can be socialized. The effectiveness of human resources is demonstrated by the equitable distribution of ASNs for each SKPD unit, for the value of money is a clean regional government and has never been published on corruption issues.